Co-creation and co-production in municipal risk governance – A case study of citizen participation in a German city. Issue 2 (1st February 2023) - Haustein, Ellen; Lorson, Peter C.
ABSTRACT: Municipal risk governance requires a communication-oriented approach that involves citizens in order to foster risk resilience. This study argues that citizen participation mechanisms enable citizens to co-create and co-produce risk governance. The paper draws on the case of a German city, including 45 interviews with experts from the municipality's administration. The results indicate that citizens play a vital role in the risk identification and risk management of institutional and social, collective risks by providing time, information, and other resources. Specific citizen participation mechanisms can even help to handle system risks by fostering acceptance and loyalty.